OCCURRENCE OF UREAPLASMA DIVERSUM IN THE GENITAL TRACT OF FEMALE BUFFALOES (BUBALUS BUBALIS) - Silva, Grasiene de Meneses; de Oliveira, Pollyanne Raysa Fernandes; de Macêdo, Allison Alves; Soares, Larice Bruna Ferreira; Borges, Jonas de Melo; dos Santos, Sandra Batista; Mota, Rinaldo Aparecido; Pinheiro Junior, José Wilton (Archives of Veterinary Science, 2020)
We investigated the occurrence of Ureaplasma diversum in the genital tract of female buffaloes. A total of 292 vaginal swab samples of buffaloes of reproductive age from nine farms were analyzed. These were distributed in five cities of Pernambuco state, Brazil. DNA was detected using polymerase chain reaction (PCR) technique. The frequency of females positive for U. diversum was 2.05% (6/292). Concerning the farms, 22.22% (2/9) of the investigated properties had at least one positive animal. Samples positive on PCR were inoculated in specific media for culturing Ureaplasma spp. However, there was no growth of characteristic colonies. This study documents the occurrence of infection by microorganisms of the species Ureaplasma diversum in the reproductive tract of buffalo females in the state of Pernambuco, Brazil. Thus, epidemiological investigations must be carried out with the presence of this microorganism should be investigated to assess the role of this pathogen as a causative agent of vulvovaginitis and abortions considering that these occurrences may decrease reproductive rates and cause negative economic impact in buffalo farming.